Underage Marriage from a Juridical and Psychological Perspective in Indonesian Society - Muhajir, Muhajir; Khasanah, Fitrohtul (CV. ULIL ALBAB CORP, 2025)
phenomenon in Indonesia despite regulations that limit the minimum age of marriage. Data shows that 11.21% of women are married before the age of 18, with higher rates in rural areas. The research aims to analyze the juridical and psychological perspectives of underage marriage in Indonesian society, as well as identify the relationship between legal implementation and the psychological impact on children. The research used a qualitative method with a descriptive-analytical approach, involving in-depth interviews with religious court judges, psychologists, and children who married early. The results show that the legal system is weak in protecting children, reflected in the high number of marriage dispensations, which reached 65,000 cases in 2021. Children who marry early experience significant psychological impacts, with 70% experiencing stress and anxiety, 50% experiencing depression, and 65% having difficulty managing household conflicts. The study concludes that an integrative approach combining legal and psychological aspects is needed to address early marriage, and that the legal system needs to be strengthened to provide better protection for children.